A Velocity Map Imaging Study of the Reactions of O+ (4S) With CH4 - Pei, Linsen; Farrar, James M. (Frontiers in Chemistry, 2019)
We present a velocity map imaging study of the key ion-molecule reactions occurring in the O+ (4S) + CH4 system at collision energies of 1.8 and 2.1 eV. In addition to charge transfer to form CH4+, we also present data on formation of CH3+, for which the experimentally determined images provide clear confirmation that the products arise from dissociative charge transfer rather than hydride transfer. Experimental data are also presented on the formation of HCO+ through a transient [OCH4]+ complex living many rotational periods. Plausible reaction pathways and intermediate structures are presented to give insight into the routes for formation of these reaction products.